Efektivitas Sistem Temu Kembali Informasi Online Public Catalog (OPAC) Dengan Tinjauan Precision Menggunakan Pendekatan Judul Dan Subjek Di Perpustakaan Universitas Muhammadiyah Bengkulu - Linda Kartina; Purwaka Purwaka; Fransiska Timoria Samosir (Pustakaloka, 2019)
Library as a centre for information resources is the backbone of the progress of an educational institution. Imbalance between the use of information retrieval system facilities advance search and a quick search of the catalogue are very  common in a search. This study was aimed to know and to describe how the precision of information retrieval system by using title field and subject on OPAC (Online Public Access Catalog) ) at Muhammaddiyah University Library of Bengkulu is effective as an information retrieval system. This study was a quantitative descriptive study using analytical methods. The technique of data collection in  this study was by using trace observation on the Online Public Access Catalog (OPAC). The study was carried out by using the title of the names of study programs and the subject to study program as the study sample a mounted to 206. Sample were taken by using purposive sampling techniques. The result of the study showed that search using advanced search features by using the section title of sociology subject obtained a precision marks of 0,98 while the use of advanced search features by using biology education subject obtainrd precision mark of 0,66. The use of quick search feature by using the sociology subjects get a precision marks of 0,98 while the use of quick search feature by using biology education subject obtained a precision marks of 0,99. The testing on the four search shows that the quick search and advanced search features in the title and subject are in the average range of 0,90 so it is said that the search system of OPAC at Muhammadiyah University Library of Bengkulu is effective as an information retrieval system.